KARAKTER MORFOLOGI BUAH EMPAT JENIS PISANG (Mussa spp) LOKAL ASAL INDRAGIRI HULU - Devi Mayawi Isna; Mardaleni; Putri Lukmanasari (UIR Press, 2024)
Riau is home to a wealth of genetic resources distributed across various regions, including local banana varieties found in Indragiri Hulu. A study titled